2021
DOI: 10.1097/j.jcrs.0000000000000397
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of cataract surgery in pseudoexfoliation syndrome in England: 10-year retrospective cohort study

Abstract: Purpose: To investigate the outcomes of cataract surgery in eyes with pseudoexfoliation syndrome in a real-world National Health Service setting. Setting: Prince Charles Eye Unit, Windsor, United Kingdom. Design: Single-center retrospective cohort study. Methods: All eyes that underwent phacoemulsification cataract surgery from January 2010 to December 2019 were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…IOP spikes occurred more often in eyes with ExG than in those with POAG (23.7% vs. 9.1%). Patients with ExG tend to have higher rates of elevated IOP than those without ExG after cataract surgery [ 29 ]. This tendency might have contributed to the significant difference in IOP spikes between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…IOP spikes occurred more often in eyes with ExG than in those with POAG (23.7% vs. 9.1%). Patients with ExG tend to have higher rates of elevated IOP than those without ExG after cataract surgery [ 29 ]. This tendency might have contributed to the significant difference in IOP spikes between the two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Results similar to our study with high incidence of zonular dialysis and dropped nucleus were also seen in 10 year retrospective cohort study done in England. 18 A study by Avramides et al had shown zonulolysis in 13.09%; posterior capsule tear in 10.71% and vitreous loss in 7.14%. 10 Another study by Joshi et al had shown intraoperative difficulties in 62 eyes (27.4%) with poor pupillary dilation being the most common problem (32 eyes, 14.2%), but zonular dehiscence (18 eyes, 8%) being the most common complication.…”
Section: Discussionmentioning
confidence: 96%
“…Bag dislocation in these situations usually occurs a long time after cataract surgery, with a mean interval of 6.9-8.5 years [9][10][11]. In silico studies shall help understand the mechanics of the IOL dislocation, and study the parameters that could influence this complication, due to its increasing incidence following the increase of procedures performed to remove cataracts [12][13][14]. However, only a few computational studies on the crystalline lens are found in literature and to the authors' knowledge there are none addressing the IOL dislocation.…”
Section: Introductionmentioning
confidence: 99%
“…This results in the reduction of the transmission of light and in scattering light, leading to blurred vision, and in the extreme to blindness, when not treated in time. Recently, the most common solution available is the complete removal of the cataract, i.e., of the crystalline lens, followed by an implant of an IOL in the capsular bag to replace it, leaving the eye in a pseudophakic state [12,22,23].…”
Section: Introductionmentioning
confidence: 99%